Contribution of Trade Facilitation Measures to the Operation of Supply Chains - Moïsé, Evdokia (OECD Trade Policy Papers, 2015)
This report assesses how specific border procedures impact on the operation of supply chains and the resulting policy implications, using data from the OECD Trade Facilitation Indicators (TFIs) database and from the OECD-WTO database on trade-in-value-added. The assessment focusses on the impact of trade facilitation measures in three areas: on the amount of foreign value-added embodied in final domestic demand; on the amount of foreign value-added embodied in the gross exports of a reference country; and on the amount of domestic value-added embodied in foreign final demand for agriculture and primary products, low tech industries, medium-low tech industries, and high and medium-high tech industries. A small increase of 0.1 in TFIs performance could potentially generate increases in a country's value-added "imports" in a range of between 1.5 and 3.5%, while in the case of "exports" these increases could range between 1 and 3%. Measures that enhance the predictability and the speed of movement of goods are critical factors that shape the sourcing decisions of companies. The impact is strongest when the value-added originates in medium-low tech industries, such as mining and quarrying or basic metals sectors, or in high and medium-high tech industries, such as transport equipment, chemicals and electrical and optical equipment, and is destined to high and medium-high tech industries. Key words: Customs, global value chains, GVCs, intermediate inputs, trade facilitation, trade flows, trade policy, transparency, simplification